Expansion and impact of cassava brown streak and cassava mosaic diseases in Africa: A review - Chikoti, Patrick Chiza; Tembo, Mathias (Frontiers in Sustainable Food Systems, 2022)
Africa produces over half of global cassava; however, the continent's average yield is below the potential yields achieved under experimental conditions. Many factors contributing to low yield include lack of quality varieties, poor soils, limited access to capital, competition for labor, as well as pests and diseases. Plant diseases are the major biotic constraints to cassava production and have caused considerable food insecurity in Africa. Although there has been some level of disease management which has contributed to the increase in cassava production, the two viral diseases: cassava mosaic disease (CMD) and cassava brown streak disease (CBSD) still claim between 30–40% and upto 70%, respectively of Africa's cassava harvest. Given the importance of the two diseases in Africa, we review the expansion of CBSD and CMD; impacts of the two diseases on food security and how they can be managed. We provide insights in the spread of the two diseases, management efforts, and future directions.